Otosclerosis surgery in a residency training program: The Oporto Hospital Center experience - Ferreira Rosa, Francisco (2017)
Objective: To evaluate the results of patients submitted to surgical treatment of otosclerosis by residentes of Otorhinolaryngology and to make a reflection on the inclusion of stapedic surgery in the residency program of Otorhinolaryngology.Materials and Methods: Retrospective study of patients submitted to surgical treatment of otosclerosis, by inpatients of Otorhinolaryngology, at the Oporto Hospital Center between January 2010 and December 2015.Results: 87 patients were included in the study, and 12 underwent bilateral surgery (performed by residents), in a total of 99 surgical procedures. The surgical success rate was 85% (air-bone gap less than 10dB). The air-bone gap was less than or equal to 20 dB in 96% of the cases. There was only one case of profound sensorineural hearing loss.Conclusions: After analyzing the literature and evaluating the results and complications obtained in this study, the authors consider that the stapes surgery can be included in the residency training program of the Otorhinolaryngology.